Prevalence and Risk Factors of Diabetic Retinopathy in a Tertiary Hospital in Padang, Indonesia - Novian Adi Saputra; Weni Helvinda; Khalilul Rahman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Diabetic retinopathy (DR) is a prevalent microvascular complication of diabetes, leading to vision impairment and blindness. This study aimed to determine the prevalence and risk factors associated with DR among patients attending a tertiary care center in Padang, Indonesia. Methods: A cross-sectional study was conducted at the eye polyclinic of Dr. M. Djamil General Hospital, Padang, Indonesia, from October 2020 to March 2021. Patients diagnosed with diabetes who underwent a comprehensive ophthalmological examination were included. Data collected included demographics, duration of diabetes, cholesterol levels, and DR status (classified as non-proliferative diabetic retinopathy (NPDR) or proliferative diabetic retinopathy (PDR)). Results: A total of 200 patients with diabetes were included. The prevalence of DR was 55%, with 40% having NPDR and 15% having PDR. Multivariate analysis revealed that longer diabetes duration (odds ratio [OR] 1.8, 95% confidence interval [CI] 1.2-2.7, p=0.004), higher cholesterol levels (OR 2.5, 95% CI 1.5-4.1, p=0.001), and older age (OR 1.1, 95% CI 1.0-1.2, p=0.03) were independently associated with the presence of DR. Conclusion: DR is highly prevalent among diabetic patients in tertiary care center Padang, Indonesia. Longer diabetes duration, elevated cholesterol, and older age are significant risk factors for DR. Early detection and management of these risk factors are crucial to prevent vision loss in this population.